Slovak Republic : 2017 Article IV Consultation-Press Release; Staff Report; and Informational Annex for Slovak Republic. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights projected moderate 2016 real GDP growth in the Slovak Republic, but still at a robust 3.3 percent. Growth continues to benefit from an improving labor market, low inflation, and strong household credit growth. The output gap is now closed. Fiscal consolidation resumed in 2016, and the fiscal deficit is estimated to have narrowed to 2 percent of GDP. The outlook is favorable, with growth expected to peak at 3.9 percent in 2019 and settle at about 3.5 percent thereafter, reflecting greater export capacity as a result of investment in the automotive industry.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet